Tantangan Pengembangan Pendidikan Keguruan di Era Global - Oviyanti, Fitri (Nadwa: Jurnal Pendidikan Islam, 2013)
Globalization barrage pass major changes to the world order as a whole. This era is characterized by the process of life worldwide, the advancement of science and technology, especially in the field of communication as well as the transformation and cross-cultural. Changes brought about by globalization are also experienced by the world of education with teachers as practitioners. Challenges faced by teachers in the global era, such as the development of science and technology are so rapid and fundamental; moral crisis that swept the nation and thestate, social crisis and a crisis of identity as a nation. All that obviously requires prospective teachers and qualified professionals. Teacher education programs must be able to provide excellent service to the students so that they can esta-blish qualified teacher. Improving the quality of education will foster public confidence that still exist in the future?Â AbstrakGlobalisasi mewariskan rentetan perubahan besar pada tatanan dunia secara menyeluruh. Era ini ditandai dengan proses kehidupan mendunia, kemajuan ilmu pengetahuan danÂ  teknologi, terutama dalam bidang transformasi dan komunikasiserta terjadinya lintas budaya. Perubahan yang dibawa oleh globalisasi ini juga dialami oleh dunia pendidikan dengan guru sebagai praktisinya. Tantangan yang dihadapi guru di era global, seperti perkembangan ilmu pengetahuan dan tekno-logi yang begitu cepat dan mendasar; krisis moral yang melanda bangsa dan negara, krisis sosial dan krisis identitas sebagai bangsa. Semua itu jelas menuntut calon guru yang profesional dan bermutu. Program pendidikan guru harusmampu memberikan pelayanan prima kepada mahasiswa sehingga mampu mencetak guru yang berkualitas. Peningkatan mutu pendidikan ini akan menumbuhkan kepercayaan masyarakat sehingga tetap eksis di masa datang.